Brahmasūtrabhāṣyam - Śrīkaṇṭhaśivācārya; Bādarāyaṇa; Hālāsyanāthaśāstri, Rā.; Appayya Dīkṣita; Appayya Dīkṣita (Dillī : Nāga Pabliśarsa, 1986)
Saiva commentary, called Śrīkaṇṭhabhāṣyā, with text of the Brahmasūtra of Bādarāyaṇa, aphoristic work on the Vedanta; with super commentaries.
Reprint. Originally published: Bombay : Nirnaya-Sagar Press, 1908-1918. Originally published in series: Bharatee Mandiram Sanskrit series.
Title on added t.p.: The Brahma sūtra bhāṣya of Śrīkanṭhacārya.
In Sanskrit.
Mode of access: Internet.
Keywords: Śrīkaṇṭhaśivācārya; Bādarāyaṇa; Śaivism -- Doctrines; Vedanta